DISEASE COPING STYLES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE OR RHEUMATOID ARTHRITIS - Y. K. Galetskayte; B. A. Volel; D. F. Pushkarev; E. A. Las (Klinicist)
Objective: to study the types of response to illness in patients with chronic obstructive pulmonary disease (COPD) or rheumatoid arthritis (RA).Subjects and methods. The sample consisted of 100 patients (mean age 59.2 ± 14.4 years) from University Clinical Hospital One, I.M. Seche nov First Moscow State Medical University, 57 of whom were treated for RA and 43 were for COPD. All the patients were examined by a psychiatrist, a psychologist, and a therapist. The Beck Depression Inventory, SF-36 quality of life questionnaire, and projective psychological tests were also used.Results. Three main types of response to illness were identified. The features of aberrant hypochondria were most common in the patientswith COPD (53.3 % (23/43)). In RA, hypochondriacal development as a confrontation with illness was intrinsic to a considerable proportion of patients (42.1 % (24/57)). The common response was hypochondriacal neurosis (health anxiety, organ neurotic and omatoautonomic disorders) that was encountered in 27 % (27/100) in the patients with COPD or RA and more common in those with RA (29.8 % (17/57)). The examination revealed nosogenic depressive reactions in 19.2 % (11/57) of the patients with RA and in 9.3 % (4/43) of those with COPD.Conclusion. The main types of response to somatic illness in the two chronic diseases similar in their impact on quality of life have been investigated, which may be further used to manage this category of patients.